Inpatient Nurses’ Perception on The Implementation of Acute Care Nursing in The Hasanuddin University Hospital - Rahmat Hidayat; Rini Rachmawaty; llkafah llkafah (Faculty of Nursing, Universitas Hasanuddin, 2019)
Introduction: Acute care is a type of time-sensitive care, this is due to an acute condition requiring rapid intervention. Acute conditions that exist in the inpatient unit would require special care in handling. This acute condition can affect many things, one of which is the patient satisfaction. With proper treatment for acute cases, the course will improve patient satisfaction itself. However, to date, acute care has been poorly defined and inadequately supported in most developing health systems. Aims of Study: This research aims to determine nurses’ perception on the implementation of inpatient acute nursing care in the Hasanuddin University Hospital. Method: This research was a qualitative method, data collection using individual interviews against ten participants (inpatient nurses) and validity checks of the data that utilizes something beyond the data. Data analyze used thematic analysis. Result: The results of the research yield four themes. Those four themes are perception of acute conditions, supporting factors in the management of patients with acute conditions, inhibiting factors in the management of patients with acute conditions, and nurses’ hope for acute care. Conclusion: From this research it is known that the incidence of acute conditions in the inpatient unit of Hasanuddin University Hospital less than chronic conditions. To handle acute cases, nurse in the inpatient unit take action early by monitoring vital signs, then immediately gave emergency action if necessary, while collaborating with the doctor. Supporting factors for nurses is the availability of emergency trolly, as well as cooperation among nurses who are good. Whereas the inhibiting factor is the number of nurses who are still lacking and the absence of code blue team. Advice from researchers, to health institutions is expected to be able to form a rapid response team (code blue), so that patients with serious/acute condition can be handled more quickly and efficiently, so that the implementation of nursing, especially nursing acute to run well and the nurse also will not experience in serving patients overwhelmed.